Enhancing Performance Through Job Involvement and Commitment in Indonesia: Meningkatkan Kinerja Melalui Keterlibatan dan Komitmen Kerja di Indonesia - Wantiningsih, Fitria Febri; Hariasih, Misti (Universitas Muhammadiyah Sidoarjo, 2024)
In the globalization era, companies need high-quality human resources to stay competitive. This study explores the impact of job involvement and organizational commitment on employee performance at CV. ESP Surya Jaya Jember, considering employee satisfaction as an intervening variable. Using a quantitative descriptive approach, data from 50 randomly selected employees were analyzed with SPSS. The findings reveal that job involvement and organizational commitment significantly enhance employee performance, while job satisfaction also positively impacts performance but does not mediate the other relationships. These results suggest that boosting job involvement and organizational commitment directly improves employee performance. Highlights: Job involvement and commitment directly enhance employee performance. Satisfaction boosts performance but doesn't mediate other variables. Focus on involvement and commitment to improve performance. Keywords: Job Involvement, Organizational Commitment, Employee Performance, Job Satisfaction, Quantitative Research